2008
DOI: 10.1002/chem.200801728
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Reactivity of C(sp3)‐Cyclometalated IrIII Compounds in Hydrogen Transfer Reactions

Abstract: The manuscript describes the synthesis and full characterization of a new PC(sp(3))P-based cyclometalated Ir(III) complex that manifests an exceptional thermal stability, as well as outstanding reactivity in hydrogen transfer reactions. The described compound represents the first example of a new family of stable C(sp(3))-metalated compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
47
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 58 publications
5
47
0
Order By: Relevance
“…Moreover, they proved themself as highly active catalysts for the transfer hydrogenation of ketones [12], as well as transfer [16] and acceptorless dehydrogenation of alcohols [17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they proved themself as highly active catalysts for the transfer hydrogenation of ketones [12], as well as transfer [16] and acceptorless dehydrogenation of alcohols [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Periana and coworkers investigated the heterolytic C À H bond activation of methane and benzene with a cyclometalated Pt II complex as well as catalytic methane hydroxylation using an Ir III NNC pincer complex in acidic solution; [7,8] another study deals with transfer hydrogenation mediated by a cyclometalated Ir III compound. [9] 2,2'-Bipyridine (bipy) and related heterocycles, which are versatile ligands in the coordination chemistry of transition metals, [10] are well suited for the formation of cyclometalated compounds. Moreover, it has been shown that cyclometalated [PtA C H T U N G T R E N N U N G (bipyÀH)] + (1) can formally dehydrosulfurize a variety of thioethers in the gas phase; [11] especially in the reaction with dimethyl sulfide, efficient oxidative C À C bond coupling and concomitant formation of neutral ethene was observed.…”
Section: Introductionmentioning
confidence: 99%
“…[9] However, a few groups have recently described promising catalytic results using N À C À N, [10] P À C À P, [10a,11] C À P, [12] and C À N À N [13] cycloruthenated or cycloiridiated [14] ligands. Our contribution to this field was triggered by the discovery that cycloruthenated chiral benzylamines are also attractive catalyst precursors for the reduction of acetophenone.…”
Section: Introductionmentioning
confidence: 99%